Identification of the Exemplary Values of Buya Ahmad Rasyid Sutan Mansur in History Learning at SMA Muhammadiyah 3 Surakarta - Ihsan Ihsan; Sariyatun Sariyatun; Djono Djono (Indonesian Academy of Social and Religious Research (IASRR), 2020)
Exemplary values ​​need to be upheld with great pride and practiced in everyday life. It must be admitted that the current exemplary value tends to decrease in practice. Therefore, exemplary values ​​need to be socialized to the younger generation through history learning. by identifying the exemplary values ​​of Buya Ahmad Rasyid Sutan Mansur into students through history learning materials. The research method in this study is a qualitative method with a Discourse Analysis approach. The strategy in this research is a single case study. Data were collected through observation, in-depth interviews, documentation. Data validity was done through source triangulation. The data analysis technique uses several stages, namely data reduction, data presentation, concluding with interactive analysis by Milles and Huberman. The results of this study indicate: (1) that Buya Ahmad Rasyid Sutan Mansur has 5 exemplary values ​​listed in Strengthening Character Education including Religious Values, Nationalism, Leadership and Struggle, Teguh Establishment, which is expected to foster exemplary values ​​in history learning by highlighting character values ​​contained in it. (2.) Obstacles Faced by Teachers in Learning History at SMA Muhammadiyah 3 Surakarta, namely inadequate learning resources, the insufficient learning time in learning, and lack of student activity levels in learning.